A Public health wound: health and work among children engaged in the worst forms of child labour in the informal sector in Dhaka, Bangladesh: a retrospective analysis of Médecins Sans Frontières occupational health data from 2014 to 2023 - Grazia Caleo; Sohana Sadique; Didem Yuce; Martins Dada; Bianca Benvenuti; Jobin Joseph; Debbie Malden; Kalyan Velivela; Salim Mahmud Chowdhury; Christabel Mayienga; Tasmia Shenjuti; Gayathrie Sadacharamani; et al. (BMC Public Health)
Abstract Background Bangladesh has the second highest burden of child labour in South Asia. The informal sector employs most of the children however, data on health including injuries and place of work for children are limited. As the deadline for the Sustainable Development Goals to end child labour is upon us, it is paramount to document the impact of child labour on health. This study aims to contribute to this knowledge gap by presenting medical data from occupational health clinics (OHCs) set up by Médecins Sans Frontières (MSF) in a peri-urban area of Dhaka, Bangladesh. Methods We did a retrospective analysis of health care records of children attending MSF OHCs between February 2014 and December 2023. We stratified the analysis by sex and age (< 14 years and ≥ 14- < 18 years). We looked at morbidities according to type of factory, whether children reported working with machinery, and examined nutritional and mental health (2018–2023) status. Results Over the study period, there were 10,200 occupational health consultations among children < 18 years, of which 4945 were new/first time consultations. The average age of children attending their first consultation was 14.7 years, of which 61% were male. Fifteen percent reported living inside the factory. Children worked in all prohibited categories of the informal sector. Almost all children reported operating machinery. Musculoskeletal (26%) and dermatological (20%) were the most identified conditions, and 7.5% of consultations were for work-related injuries. A higher proportion of male children had injuries (11% vs 2.5% in girls). Children working in metal factories accounted for most injuries (65%). Mood-related disorders accounted for 86% of the 51 mental health consultations. Half of all children were malnourished with higher levels in boys and those < 14 years. Conclusions Findings suggest that children face hazardous realities; engaged in the worst form of labour, bearing important morbidity and injury burden, with vulnerabilities varying by sex and age. Despite their economic contributions to the informal sector, they remain largely invisible and exploited. This study highlights the urgent need for child rights-based research and cross-sectoral approaches that actively involve children to develop sustainable, targeted solutions to eliminate child labour.